Dust Unveils the Formation of a Mini-Neptune Planet in a Protoplanetary Ring - Pérez, Sebastián; Casassus, Simon; Baruteau, Clément; Dong, Ruobing; Hales, Antonio; Cieza, Lucas (The Astronomical journal, 2019)
Rings and radial gaps are ubiquitous in protoplanetary disks, yet their possible connection to planet formation is currently subject to intense debates. In principle, giant planet formation leads to wide gaps that separate the gas and dust mass reservoir in the outer disk, while lower mass planets lead to shallow gaps that are manifested mainly on the dust component. We used the Atacama Large Millimeter/submillimeter Array (ALMA) to observe the star HD 169142, host to a prominent disk with deep, wide gaps that sever the disk into inner and outer regions. The new ALMA high-resolution images allow for the outer ring to be resolved as three narrow rings. The HD 169142 disk thus hosts both the wide gap trait of transition disks and a narrow-ring system similar to those observed in the TW Hya and HL Tau systems. The mass reservoir beyond a deep gap can thus host ring systems. The observed rings are narrow in radial extent (width/radius of 1.5/57.3, 1.8/64.2, and 3.4/76.0 in au) and have asymmetric mutual separations: the first and middle ring are separated by 7 au while the middle and outermost ring are distanced by ∼12 au. Using hydrodynamical modeling we found that a simple explanation, involving a single migrating low-mass planet (10 M⊕), entirely accounts for such an apparently complex phenomenon. Inward migration of the planet naturally explains the ring's asymmetric mutual separation. The isolation of HD 169142's outer rings thus allows a proof of concept to interpret the detailed architecture of the outer region of protoplanetary disks with low-mass planet formation of mini-Neptune's size, i.e., as in the protosolar nebula.